Improving the quality of surgical morbidity and mortality conference using a standardized reporting and assessment tool: a validation study from a large academic medical center in the United States - Sarah M. Dermody; Marc C. Thorne; Robert J. Morrison (Patient Safety in Surgery)
Abstract Background The purpose of this study is two-fold: (1) Improve the quality of Morbidity and Mortality conferences by developing a standardized presentation template and assessment tool; (2) Assess the intervention impact by comparing pre- and post-intervention data. Methods A pre-post study was conducted at a tertiary care academic medical center between January 2022– January 2023. A standardized presentation template was created and a short assessment tool was developed to evaluate the quality of presentations on eight domains. We hypothesized that development of this template would significantly improve the quality of M&M conferences. Pre- and post-intervention data were compared using the Kruskal-Wallis test to evaluate for significant differences. Effect sizes for each domain were assessed by Cohen’s d. Results A total of 127 pre-intervention responses and 61 post-intervention responses were received over a six-month period. Statistically significant increases in post-intervention scores were noted in nearly all presentation domains, including clarity of case selection rationale, nature of the safety event, circumstances leading to the safety event, contributing factors, understanding of the safety event, and anticipated benefits to patient outcomes (p < 0.05). The effect sizes ranged from medium for rationale for case selection to small for the identification of corrective actions. Conclusions The introduction of a standardized, guided template improved the quality of Morbidity and Mortality presentations, with medium effect sizes and statistically significant increases in nearly all surveyed domains. A ceiling effect in the overall assessment score was noted as presentations prior to the intervention were rated highly. Standardization of case selection and presentations can promote alignment of the Quality Improvement Morbidity and Mortality workflow with broader-scope initiatives, departmentally and institutionally.